Pengaruh PMT Biskuit Sandwich Terhadap Ibu Hamil Kurang Energi Kronis di Puskesmas Bantarbolang Kabupaten Pemalang - Nanik Setiyowati; Yuliana Noor Setiawati Ulvie (Universitas Muhammadiyah Semarang, 2019)
The risk chronic energy deficiency of pregnant can occur after miscarriage, premature birth, birth defects, low birth weight babies and even infant mortality. Pregnant women, physical growth (stunting), brain and growth that causes non-communicable diseases in adulthood. Nutrition intervention strategies for chronic energy deficiency of pregnant. Food choice categories, counseling, education, cooperation and coordination withhealth workers and related sector workers. The form of supplementary food for chronic energy deficiency of pregnant can consist of local food or manufacturers and nutrient-dense drinks. Sandwich purpose towardsnutritional status for chronic energy deficiency of pregnant at Bantarbolang Health Center, Pemalang Regency. This type of research is a quasi-experimental design with one group pre and posttest design. The research sample was 29 trimester chronic energy deficiency of pregnant as many as 29 pregnant women who were measured for Upper Arm Circumference (LiLA) before and after the provision of assistance, namely giving extra biscuit sandwiches for 3 months (90 days). Furthermore, LiLA measurements are carried out every month,30 days, 60 days, 90 days after supplementary feeding biscuit sandwiches. The independent variable is PMT biscuit sandwich and the independent variable is nutritional status of chronic energy deficiency of pregnant.The statistical test used was the Wilcoxon test. The results of univariate analysis, the average LiLA before providing sandwich biscuits were 21,879 cm ± 1,286 cm and the average LiLA given PMT was 22.4 cm ± 1.31 cm. Statistical test results obtained from the addition of sandwich sandwiches with increased nutritional status (LiLA) of chronic energy deficiency of pregnant (p = 0,000). Giving extra sandwich biscuits further increases the nutritional status of chronic energydeficiency of pregnant. Keywords: chronic energy deficiency of pregnant, Supplementary Feeding, sandwich biscuits